Mawar Hitam Sebagai Simbol Kematian Estetik: Analisis Semiotika Fenomena Viral Bunuh Diri di Jembatan Cangar dalam Lanskap Digital - Kiki Malika Primadani; Suhardi Suhardi (Belantika Pendidikan, 2026)
Abstract: The "Black Rose" suicide phenomenon at Cangar Bridge, Malang, 2026, is analysed through Roland Barthes's semiotic framework. Objects left at the scene a motorcycle, sandals, cigarettes, a lighter, and a registration document function as sign systems operating across denotation, connotation, and myth. Using qualitative-interpretive and social semiotic approaches, this study reveals how digital framing constructs an "aesthetic death" narrative, amplifying the Werther Effect through FOMO mechanisms. These objects become "silent witnesses" whose meanings are algorithmically amplified across platforms. The "Black Rose" label constitutes second-order Barthesian myth production that romanticises mental health crises, with implications for digital regulation, media literacy, and responsible reporting. Abstrak: Fenomena bunuh diri "Mawar Hitam" di Jembatan Cangar, Malang, 2026, dianalisis menggunakan kerangka semiotika Roland Barthes. Benda-benda yang ditinggalkan seperti sepeda motor, sandal, rokok, korek api, dan STNK berfungsi sebagai sistem tanda yang beroperasi dalam denotasi, konotasi, dan mitos. Melalui pendekatan kualitatif-interpretatif dan analisis semiotika sosial, penelitian ini mengungkap bagaimana pembingkaian digital membangun narasi "kematian estetis" yang memperkuat Efek Werther melalui mekanisme FOMO. Benda-benda tersebut menjadi "saksi bisu" yang maknanya diperkuat algoritma platform digital. Label "Mawar Hitam" merupakan produksi mitos tingkat kedua Barthes yang meromantisasi krisis kesehatan mental, dengan implikasi pada regulasi digital, literasi media, dan protokol pemberitaan yang bertanggung jawab.